Association of elevated α-defensin levels with interstitial pneumonia in patients with systemic sclerosis. Issue 1 (December 2015) - Sakamoto, Noriho; Kakugawa, Tomoyuki; Hara, Atsuko; Nakashima, Shota; Yura, Hirokazu; Harada, Tatsuhiko; Ishimoto, Hiroshi; Yatera, Kazuhiro; Kuwatsuka, Yutaka; Hara, Toshihide; Ichinose, Kunihiro; Obase, Yasushi; et al.
Abstract Background Interstitial lung disease (ILD) is the leading cause of mortality in patients with systemic sclerosis (SSc). Although the pathogenesis of SSc-ILD is not well understood, neutrophils may play a pivotal role in this process. Neutrophils store azurophil granules that contain defensins, antimicrobial peptides that function in regulating the inflammatory response, and IL-8, a potent chemoattractant for neutrophils. The present study evaluated the levels of defensins and IL-8 in patients with SSc-ILD to determine their roles in disease pathogenesis. Methods Defensins (also known as human neutrophil peptides, HNPs) and IL-8 levels were measured in the serum and bronchoalveolar lavage fluid (BALF) of 33 patients with SSc-ILD and in 20 healthy controls by using ELISA. Results BALF analysis revealed a significant increase in HNPs in SSc-ILD patients (median; 240.0 pg/mL) than that of healthy controls (79.7 pg/mL). Additionally, IL-8 levels were higher in SSc-ILD patient serum and BALF as compared to healthy controls (16.4 pg/mL vs. 5.8 pg/mL and 15.4 pg/mL vs. 14.5 pg/mL, respectively). However, plasma HNPs levels were relatively unchanged. HNP and IL-8 levels in patient BALF displayed a significant positive correlation significantly correlated (r = 0.774, p <0.01), and which also correlated with clinical disease parameters—such as ILD biomarkers, pulmonary function tests, ratio of neutrophils and eosinophils in BALF, tricuspid regurgitation peak gradient (TRPG), and the extent of high-resolution computed tomography (HRCT) findings in the lung. Levels of plasma HNPs and serum IL-8 did not show a significant correlation with any clinical parameter. SSc-ILD progression was evaluated by pulmonary function tests, but no association was observed between VC change ratios and HNPs or IL-8 levels. Conclusions BALF levels of HNPs and IL-8 were higher in SSc-ILD than in healthy controls, and are associated with various clinical disease parameters. Further studies are needed to clarify the role of defensins and IL-8 in SSc-ILD pathogenesis.